THE EFFECT OF MORINGA OLEIFERA L PENGARUH EKSTRAK DAUN KELOR (MORINGA OLEIFERA) TERHADAP PRODUKSI ASI DAN PENINGKATAN BERAT BADAN BAYI - Putri, Widi (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: Exclusive breastfeeding is giving only breast milk without giving other food and drinks to babies until they are 6 months old, except for medicine and vitamins. Failure to provide exclusive breastfeeding is influenced by various factors such as the assumption of low breast milk production, inadequate nutritional intake, low education, lack of knowledge, and lack of husband and family support. Purpose:To determine the effect of Moringa oleifera leaf extract on breast milk production in postpartum mothers and baby weight gain. Method: This Evidence Based Case Report (EBCR) was carried out by searching the literature in several articles such as Science Direct, PubMed, Garuda Portal, Google Scholar according to predetermined criteria. Results: An evaluation was carried out on the 3rd day of giving Moringa leaf extract capsules, there was an increase in breast milk volume of 38 ml and an increase in the baby's weight of 70 grams. Conclusion: There was an effect of giving Moringa oleifera leaf extract on breast milk production and the baby's weight gain.